PEMBERLAKUAN ASAS KELESTARIAN DAN KEBERLANJUTAN DALAM PEMBUKAAN LAHAN DI HUTAN (ULASAN KASUS VONIS PENGADILAN NEGERI PEKANBARU DENGAN NOMOR 1215/PID.B/2016/PN.PBR) - Tamada Xio Fortune; Mella Ismelina F. R. (Jurnal Hukum Adigama, 2020)
Woodlands are the breathing apparatus of this planet and a place to live for various animals and plants. Forest areas become areas that really need to be monitored and protected in their use. Indonesia has regulations to support the management as well as safeguard of forest areas in this country.  The regulation is Law of the Republic of Indonesia Number 32 Year 2009 focus on Environmental Safeguard and Administration. The regulation has the basis stated in the regulation to be the basis for the application of the law. The principle of sustainability and sustainability is intended to make everyone responsible for future generations and for each other in one generation by making efforts to preserve the carrying capacity of ecosystems and improve the quality of the environment. Law enforcement and enforcement of environmental destruction must be carried out based on these principles to control the damaged environmental conditions because it is related to future generations. Anthropocentrism theory proves that humans easily damage the environment because humans feel that humans are the center of living things. In practice, the implementation and enforcement of environmental regulations does not use the principles of sustainability and sustainability as a basis. The obligation to restore the environment to the depreciation done is not visible in the implementation and enforcement of these regulations for perpetrators of forest fires. Recovery of environmental damage is the implementation of the principles of sustainability and sustainability.